2012
DOI: 10.1111/php.12010
|View full text |Cite
|
Sign up to set email alerts
|

The Reversibility of UV‐B Induced Alterations in Optical Properties of the Rabbit Cornea Depends on Dose of UV Irradiation

Abstract: Solar UVB radiation evokes photokeratitis, accompanied by increased corneal hydration and changes in corneal transparency, resulting in increased light absorption. Corneal optical properties are disturbed and visual acuity decreased. The aim of this study was to investigate the reversibility of these UVB-induced changes. Rabbit corneas were irradiated with UVB doses of 0.5 J cm(-2) or 1.01 J cm(-2) during 4 days. Some rabbits were sacrificed after the last irradiation and some 2 months later. Corneas were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…As to lens damage, Bergmanson and Soderberg [27] reported that lens proteins changed after extended low doses of UVR exposure. Other studies have reported that a dose of 3.12 kJ/ m 2 UVB radiation had harmful effects on the lenticular tissue of rabbit eyes [28,29]. Moreover, Mody et al [30] reported that lens damage in albino rats would be larger under repeated exposure compared to a single exposure of the same dose of UVB.…”
Section: Discussionmentioning
confidence: 94%
“…As to lens damage, Bergmanson and Soderberg [27] reported that lens proteins changed after extended low doses of UVR exposure. Other studies have reported that a dose of 3.12 kJ/ m 2 UVB radiation had harmful effects on the lenticular tissue of rabbit eyes [28,29]. Moreover, Mody et al [30] reported that lens damage in albino rats would be larger under repeated exposure compared to a single exposure of the same dose of UVB.…”
Section: Discussionmentioning
confidence: 94%
“…The technique was reported for rabbits in the 1950s (24) and provides an objective assessment of any compromise of the cornea since this will be expected to result in an increase in corneal thickness. Pachymetry is the logically preferred method for objective assessment of UV-B-induced cornea edema (rather than simply assigning a grade) and has been used in numerous rabbit studies to assess the effects of UV-B exposure (8,15,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). The assessments of corneal thickness do not need to be made by optical pachymetry on the living eye for an alternative is to use an ultrasound pachymeter.…”
Section: Specialized In Vivo or Ex Vivo Assessments Of The Rabbit Cormentioning
confidence: 99%
“…A very different method has been used in UV‐B‐related studies in which the most superficial cells of the corneal epithelium are removed from the living eye onto a special filter membrane or paper. This can then be stained to visualize the cells and/or enzyme activities or metabolites in the cells; the technique is called corneal impression cytology .…”
Section: Specialized In Vivo or Ex Vivo Assessments Of The Rabbit Cormentioning
confidence: 99%
“…It is well established that UV radiation can be harmful to ocular structures [ 18 ]. More than two thirds of UV light applied to the cornea is transmitted through the tissue and can reach the intraocular structures, with similar transmittance values reported for human [ 19 ] and rabbit eyes [ 20 ]. While light of longer wavelengths primarily causes thermal injury, UV light causes predominantly photochemical damage, i.e.…”
Section: Discussionmentioning
confidence: 55%